A novel method to continuously monitor litter moisture – A microcosm-based experiment. (April 2015) - Wang, Lixin; Throop, Heather L.; Gill, Timothy
Abstract: Litter decomposition is a key biogeochemical process that strongly affects carbon and nutrient cycling. Our understanding of the controls over decomposition in arid and semi-arid systems is currently limited by a lack of capability to measure or predict litter moisture. Despite its potential importance in controlling litter decomposition, litter moisture has rarely been continuously monitored due to the technical constraints in doing so. The objective of this study was to test the feasibility of using inexpensive, commercially available relative humidity (RH) loggers (iButtons) to continuously estimate the litter moisture. We incubated two types of litter (conifer and broadleaf) in microcosms and tested RH-litter moisture relationships during a series of dry-down events. The results showed that we could successfully predict litter gravimetric moisture using iButton RH measurements. Highlights: We developed and tested a new method to continuously estimate litter moisture. We demonstrated the possibility of the method's application in the field. This method will contribute to the advance of dryland litter decomposition study.